Human Geminin promotes pre-RC formation and DNA replication by stabilizing CDT1 in mitosis - Ballabeni, Andrea (Nature Publishing Group, 2004)
Geminin is an unstable inhibitor of DNA replication that negatively regulates the licensing factor CDT1 and inhibits pre-replicative complex (pre-RC) formation in Xenopus egg extracts. Here we describe a novel function of Geminin. We demonstrate that human Geminin protects CDT1 from proteasome-mediated degradation by inhibiting its ubiquitination. In particular, Geminin ensures basal levels of CDT1 during S phase and its accumulation during mitosis. Consistently, inhibition of Geminin synthesis during M phase leads to impairment of pre-RC formation and DNA replication during the following cell cycle. Moreover, we show that inhibition of CDK1 during mitosis, and not Geminin depletion, is sufficient for premature formation of pre-RCs, indicating that CDK activity is the major mitotic inhibitor of licensing in human cells. Taken together with recent data from our laboratory, our results demonstrate that Geminin is both a negative and positive regulator of pre-RC formation in human cells, playing a positive role in allowing CDT1 accumulation in G2–M, and preventing relicensing of origins in S–G2.